Respostas bioquímicas e comportamentais de peixe-zebra (Danio rerio) expostos a imidacloprido: avaliação do dano oxidativo e perfil antioxidante - Guerra, Luciana Joner (2019)
Pesticides are the biggest polluters of water and soil and can reach non-target organisms such as fish. Indiscriminate application of products has been a serious concern and Brazil is one of the countries that uses the most chemicals to control agricultural pests. Imidacloprid (IMI) is one of the most commonly used insecticides in the world, such as a neonicotinoid. Although already found in several watercourses in the southern region, studies are needed on its toxic potential. Zebrafish (Danio rerio), popularly known as "paulistinha", has been the target of a program that can be compared with rodents, we can mention the ease of maintenance, manipulation and a possibility to have their rules of behavior and biochemical. In this context, researches may be performe to avaluete effects of environmental contamination. Present indicator may be related to biochemical and behavioral in zebrafish exposed for 96 h in 3 different concentrations of IMI (0.15, 15 and 45 μg L-1). Effect of S-transferase (GST) activation was increases in zebrafish brains when exposed to IMI in the combinations of 0.15 and 45 μg L-1. Carbonylated protein (CP) levels increased significantly in IMI 15 and 45 μg L-1. Nonprotein protein levels (NPSH) and lipid peroxidation levels measured by the quantification of malondialdehyde (MDA) formation were not alter over time after exposure at the concentrations tested. Exposure to IMI increases freezing time, decreases episodes and time of erratic moviment. In addition, it decreases the distance traveled, such as transitions and time in the area above the high turns used. In conclusion, the results are relevant for the exposure of biochemical and behavioral parameters in zebrafish.